Novel possibilities of acceleration time series for performance and acute fatigue assessment in uphill trail running - Montull, L.; Matas, S.; Canton, A.; Vives, E.; Solé, A.; Borrallo, A.; Ensenyat, A. (Sports Biomechanics, 2025)
The potential for assessing performance and acute fatigue in uphill trail running (UTR) through acceleration time series remains underexplored. For this purpose, time-variability of body acceleration and covariation among limb acceleration were studied in UTR. Twenty competitive and young trail runners participated in a simulation UTR test covering a distance of 4758 meters, with a total elevation gain of 575 meters and an average slope of 13.6%. Four sections with clear slope differences were identified. Detrended Fluctuation Analysis of upper back acceleration and Principal Component Analysis among wrists and ankle acceleration were performed for the whole test and for each section.